Effects of Cadmium on Escherichia Coli and Bacillus Cereus growth - N Kalantari; I Nahvi; AA Moshtaghi (Majallah-i Dānishgāh-i ̒Ulūm-i Pizishkī-i Bābul, 2000)
Objective: Although trace elements are essential nutrients for microorganisms, as high concentration they can be toxic for their growth and modify their metabolic patterns as well. In order to find out the influence of cadmium on gram negative and gram-positive bacterial cell growth, the present investigation has been undertaken. Methods: A series of experiments, E.coli and B.cereus cells have been incubated in nutrient broth medium with and without (0.01, 0.05, 0.1 mM/li) cadmium chloride for 5 hours at 37°C. Growth of bacterial cells has been assay by spectrophotometry every 30 minutes. Findings: The results obtained showed that addition of 0.01 mM/li of CD2+ in the medium inhibits B.cereus growth to 41.1%, with no effect on E.coli growth. In comparison with control, in concentration of 0.05 mM/li CD2+, growth of E.coli has been decreased to 87.5% after 3.5 hours of incubation. But this concentration of CD2+ is inhibitory to growth of B.cereus. Conclusion: This finding suggested the important role of concentration of trace elements in microorganism’s behaviors. In comparison with E.coli, B.cereus is more susceptible to cadmium.